Validation of phytosterol analysis by alkaline hydrolysis and trimethylsilyl derivatization coupled with gas chromatography for rice products. (September 2021) - Islam, Md. Atiqual; Jeong, Beom-Gyun; Kerr, William L.; Chun, Jiyeon
Abstract: In this study, the alkaline hydrolysis and trimethylsilyl derivatization method coupled with gas chromatography-flame ionization detection was validated for phytosterol analysis and then applied for determination of major phytosterols (β-sitosterol, campesterol, and stigmasterol) in rice products highly consumed in Asian countries. Recoveries of three phytosterols from brown rice, rice bran oil and standard reference material-3251 were 87.6–104.4%, 87.7–107.6%, and 92.6–99.1%, respectively, showing good accuracy of analysis. Excellent precision of phytosterol analysis was achieved from repeatability (RSD <4%), reproducibility (RSD <8%) and HorRat ratio (0.3 ≤ HorRatr /HorRatR  ≤ 1.0). Limit of quantitation of phytosterol analysis was 0.08–0.09 mg/100 g, showing high sensitivity of analysis. The total phytosterol contents (sum of major phytosterols) of rice products ranged from 18.88 to 1375.47 mg/100 g, which was high in the order of rice bran oil, rice germ, brown rice, rice with large germ, white rice and puffed rice. β-Sitosterol was the most predominant phytosterol in all rice products, which composed about 58.4–63.6% of the total phytosterols. White rice showed much lower phytosterol levels than brown rice and rice bran oil. However, it could be a good source of phytosterols because of the quantity daily consumed. Graphical abstract: Image 1 Highlights: A simple derivatization-GC method was validated for phytosterol analysis. Phytosterol analysis for rice products showed excellent accuracy and precision. β-Sitosterol was predominant phytosterol in all rice products. White and brown rice could be significant sources of functional phytosterol.